2021
DOI: 10.1007/s10120-021-01172-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of non-Helicobacter pylori helicobacter infections in Helicobacter pylori-negative gastric MALT lymphoma pathogenesis and efficacy of eradication therapy

Abstract: Background Eradication therapy is known to be effective against Helicobacter pylori-positive gastric MALT lymphoma but predicting the efficacy of eradication therapy against Helicobacter pylori-negative gastric MALT lymphoma is difficult. Recent reports have shown that non-Helicobacter pylori helicobacter infections induce gastric MALT lymphoma, and we aimed to clarify whether non-Helicobacter pylori helicobacter infections are associated with the efficacy of eradication therapy. Methods We analyzed eradicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 40 publications
2
34
1
Order By: Relevance
“…Effects of antibiotics were particularly observed in patients with localized disease [34,35]. In addition, Helicobacter species other than H. pylori have been suspected to explain the antibiotic treatment responses [36,37]. In the present study, nine H. pylori negative patients were treated with antibiotics (stage I, n = 6; stage II, n = 2; stage IV, n = 1).…”
Section: Discussionmentioning
confidence: 79%
“…Effects of antibiotics were particularly observed in patients with localized disease [34,35]. In addition, Helicobacter species other than H. pylori have been suspected to explain the antibiotic treatment responses [36,37]. In the present study, nine H. pylori negative patients were treated with antibiotics (stage I, n = 6; stage II, n = 2; stage IV, n = 1).…”
Section: Discussionmentioning
confidence: 79%
“…Bone marrow involvement is exceedingly rare (3%) [ 18 ]. There is an increasing trend of H. pylori -negative gastric MALT lymphoma cases, accounting for 6–40% of recent cases [ 7 , 8 , 9 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Compared to H. pylori -positive cases, H. pylori -negative gastric MALT lymphomas tend to be in an advanced clinical stage [ 24 ].…”
Section: Clinicopathological Features Of Gi Lymphomasmentioning
confidence: 99%
“…In H. pylori -negative cases, non- H. pylori Helicobacters (NHPHs; also referred to as H. heilmannii ) are occasionally associated with gastric MALT lymphoma [ 46 ]. Takigawa et al reported that 55% of patients with H. pylori -negative gastric MALT lymphoma without a BIRC3-MALT1 chimeric transcript are infected with an NHPH [ 20 ]. NHPHs typically have a large spiral-shaped morphology and comprise H. suis, H. felis, H. bizzozeronii, H. salomonis, and Candidatus H. heilmannii , accounting for only 0.1% of cases in which gastric biopsy is performed [ 47 , 48 ].…”
Section: Pathogenesis In Relation To Bacterial Infection or Chronic Antigenic Stimulationmentioning
confidence: 99%
See 2 more Smart Citations